2022
DOI: 10.24083/apjhm.v17i1.1085
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Personal Hygienic Practices of Rural People in the COVID-19 Situation

Abstract: Background: The study attempted to understand rural Bangladesh's health information, awareness level, and preventive measures in the Coronavirus disease -19 (COVID-19) pandemic. Methods: A cross-sectional survey by face-to-face interview was conducted with rural people from 14 June 2020 to 13 August 2020. An ordered logistic regression model was employed for data analysis. A total of 3,007 people (Female = 55.97%; Male = 44.03%) participated in the survey who met the inclusion criteria. Results: The demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…They also might have a fixed routine schedule due to their working hours leading to positive impact on their children's physical activity and rest. These present results were in harmony with Baral et al (2022) who reported that employed mothers experienced maximum level of precaution measures compared to housewives. Inconsistently, Keyworth et al (2021) stated that employed mothers were less likely to adequately follow precaution measures because of the burden of having to work at home while taking care of their children.…”
Section: Discussionsupporting
confidence: 92%
“…They also might have a fixed routine schedule due to their working hours leading to positive impact on their children's physical activity and rest. These present results were in harmony with Baral et al (2022) who reported that employed mothers experienced maximum level of precaution measures compared to housewives. Inconsistently, Keyworth et al (2021) stated that employed mothers were less likely to adequately follow precaution measures because of the burden of having to work at home while taking care of their children.…”
Section: Discussionsupporting
confidence: 92%
“…Pada hipotesis 1-4 menguji pengaruh langsung kesadaran pribadi, pengetahuan, persepsi pribadi masyarakat, serta pengetahuan dan juga pemahaman kampanye pemasaran sosial pada sikap mengarah krisis. Hasil penelitian ini mendukung penelitian-penelitian sebelumnya dari Baral, et al, (2022); Srivastava (2019); dan Wiese & Akareem (2020). H1 menghasilkan nilai sig.…”
Section: Pengujian Reliabilitasunclassified